The Bau Nyale Tradition of the Sasak Tribe on the Island of Lombok Reviewed from the Rules of Isti'maalu An-Naas Hujjatun Yajibu Al-'Amalu Bihaa - Uswatun Hasanah; Fajar Nurfigiantoro; Anta Mu’min Badji; Marwiyah (Walidem Institute and Publishing (WIP), 2024)
The purpose of this study is to analyze the Bau Nyale tradition among the Sasak Tribe people on the island of Lombok from the perspective of the fiqhiyah principle